Aplicación de los parámetros farmacocinéticos/farmacodinámicos (PK/PD) en la optimización terapéutica de los antimicrobianos. - Ambros, L.A. (2021)
Intensive use of antimicrobials (ATM), both in human and veterinary medicine, have produced an increase of resistance levels in bacteria strains. This scenario is worse when considering that ATM are a scarce resource and that there is no new ATM in the market. However, ATM still are essential tools for infection control or eradication. So, in order to preserve ATM efficacy, therapeutic strategies involving knowledge of bacteria susceptibility and ATM pharmacological data from different animal species are mandatory.\nRelationships between pharmacokinetic and pharmacodynamic ATM features, named PK/PD predictors, are effective for attain efficacy in infection treatment and, also to minimize bacterial resistance emergence.\nWe have studied the pharmacokinetic behaviour of many ATM agents (betalactams, fluoroquinolones, aminoglycosides, macrolides, lincosamides, etc.) in different domestic animal species (dogs, cats, goats, llamas) administered through different routes (IV, IM, SC, oral, intramammary) and using different formulations (soluble or sustained release injectable forms, tablets).\nPlasma, milk and tissue ATM concentrations were evaluated. Disposition curves were done and pharmacokinetic parameters were calculated. \nPK/PD predictors were estimated and ATM therapeutic recommendations for each animal species were suggested.